L'amant de la Chine du Nord - Duras, Marguerite (Gallimard, 1991)
SommaireLe Chinois et l'adolescente. Le dernier avatar des amours indochinoises d'une auteur douée pour les tragédies familiales. Roman inspiré et provoqué par le scénario et la mise en images d'un précédent roman de l'auteure, « L'amant »…»– [SDM]
Section: 237 pages ; 21 cm
Keywords: arts; asie; cours; discipline; indochine; lit3220; littérature; premier cycle; roman; régions géographiques; sexualité; thématiques; vietnam; écriture des femmes*; études littéraires

From mastery to analysis: Theories of gender in psychoanalytic feminism - Elliot, Patricia (Cornell University Press, 1991)
Critique des approches psychanalytiques en études féministes et de l'hystérie (Kristeva, Irigaray, Chodorow, Dinnerstein, Mitchell, Lacan, Freud) Voir le compte-rendu: Williams, C. L. (1992). [Review of From Mastery to Analysis: Theories of Gender in Psychoanalytic Feminism., by P. Elliot]. Contemporary Sociology, 21(5), 728–729. https://doi.org/10.2307/2075599
Keywords: 1900-1999; corps; cours; discipline; europe; fem1000; france; maternité; premier cycle; psychanalyse; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sexualité; thématiques

A lure of knowledge: Lesbian sexuality and theory - Roof, Judith (Columbia University Press, 1991)
Lesbianism in literature has been dealt with rather indirectly in the past. Editors have led readers to the "artistry" of a work containing lesbianism, emphasizing instead the literary history and historical context of the work rather than the representations of lesbianism. The editor for Colette's The Pure and the Impure, for instance, affirms that Colette has a knowledge of a "strange sisterhood," but assures readers she has never strayed from the "normal." In the groundbreaking A Lure of Knowledge, Judith Roof demonstrates that representations of lesbian sexuality occupy specific locations or positions in the arguments, subject matter, and rhetoric of Western European and American literary criticism. She examines the political context of representations: how lesbian sexuality is used as a signifier an why it appears when and where it does. Roof argues that attempts to depict or explain lesbian sexuality spur anxieties about knowledge and identity. In reaction to and denial of these anxieties, lesbian sexuality is represented in film, literature, theory, and criticism as foreplay, as simulated heterosexuality, as erotic excess, as joking inauthenticity, as artful compromise, or as masculine mask in a specific repertoire of neutralization and evasion. Challenging the heterosexism of film theory and feminist theory, this book analyzes the rhetorical use of lesbian sexuality. Roof explores a range of discourses, from the woks of such authors as Anais Nin, Olga Broumas, Julia Kristeva, Jane Rule, Luce Iriguray, and Sigmund Freud, to films such as Emmanuelle, Desert Hearts, Entre Nous, and I've Heard the Mermaids Singing, to professional tennis.
Keywords: approches et analyses; arts; cinéma; communication; discipline; hétérosexisme; lesbianisme; personnes lesbiennes; sexualité; sexualité lesbienne; systèmes d'oppressions; thématiques; études culturelles; études littéraires